p53 Activates the Long Noncoding RNA Pvt1b to Inhibit Myc and Suppress Tumorigenesis - Olivero, Christiane E.; Martínez-Terroba, Elena; Zimmer, Joshua; Liao, Clara; Tesfaye, Ephrath; Hooshdaran, Nima; Schofield, Jeremy A.; Bendor, Jordan; Fang, Dorthy; Simon, Matthew D.; Zamudio, Jesse R.; Dimitrova, Nadya (Molecular cell, 2020)
The tumor suppressor p53 transcriptionally activates target genes to suppress cellular proliferation during stress. p53 has also been implicated in the repression of the proto-oncogene Myc, but the mechanism has remained unclear. Here, we identify Pvt1b, a p53-dependent isoform of the long noncoding RNA (lncRNA) Pvt1, expressed 50 kb downstream of Myc, which becomes induced by DNA damage or oncogenic signaling and accumulates near its site of transcription. We show that production of the Pvt1b RNA is necessary and sufficient to suppress Myc transcription in cis without altering the chromatin organization of the locus. Inhibition of Pvt1b increases Myc levels and transcriptional activity and promotes cellular proliferation. Furthermore, Pvt1b loss accelerates tumor growth, but not tumor progression, in an autochthonous mouse model of lung cancer. These findings demonstrate that Pvt1b acts at the intersection of the p53 and Myc transcriptional networks to reinforce the anti-proliferative activities of p53. [Display omitted] •Pvt1b is a p53-dependent lncRNA isoform, induced by genotoxic and oncogenic stress•Production of Pvt1b RNA represses Myc transcription in cis•Pvt1b suppresses Myc transcriptional program and cellular proliferation•Pvt1b limits tumor growth, but not tumor progression, in a mouse lung tumor model Olivero et al. identify the conserved lncRNA isoform Pvt1b as a locus-specific transcriptional regulator that serves to repress Myc transcription during the p53-mediated response to stress. Production of the Pvt1b RNA inhibits cellular proliferation and tumor growth, revealing tumor suppressor activities for this cancer-associated lncRNA.